2020
DOI: 10.1093/geronb/gbaa210
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pandemic Ageism Toward Older Adults Predicts Behavioral Intentions During the COVID-19 Pandemic

Abstract: Objectives During the coronavirus disease 2019 (COVID-19) pandemic, older adults have been disproportionately affected by high rates of health complications and mortality. Reactions toward older adults included a mix of prosocial behaviors and ageist responses, consistent with the history of positive and negative views and treatment of older adults in the United States. Methods In a two-part study ( n = 113, M age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…However, the stereotype of competence (particularly incompetence) failed to have any effect on reducing hostile ageism in our study, which is contrary to the BIAS map. For example, Lytle et al ( 2020 ) found that younger adults who viewed older adults as incompetent showed more intention to help under COVID-19 circumstances. We suspect that this might be because older adults were barely acknowledged as competent especially under COVID-19 circumstances (Fraser et al, 2020 ; Shahid et al, 2020 ), while our materials were also about patients in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, the stereotype of competence (particularly incompetence) failed to have any effect on reducing hostile ageism in our study, which is contrary to the BIAS map. For example, Lytle et al ( 2020 ) found that younger adults who viewed older adults as incompetent showed more intention to help under COVID-19 circumstances. We suspect that this might be because older adults were barely acknowledged as competent especially under COVID-19 circumstances (Fraser et al, 2020 ; Shahid et al, 2020 ), while our materials were also about patients in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented the strong positive association between scarcity of resources (e.g., access to employment) and stereotyping (Leslie et al., 2014). During the COVID‐19 pandemic, the United States faced a record 14.8% unemployment rate (CRS, 2021) as millions of Americans simultaneously competed for employment and COVID‐19 related healthcare services such as access to COVID‐19 testing, mental health services, and COVID‐19 related hospitalization (Carter et al., 2020), all of which could have created a sociopolitical climate with increased stereotyping and prejudice (Lytle et al., 2020; Monahan et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Now only part of the focus of the special collection, six articles address specific vulnerabilities for older adults during the pandemic ( Avidor et al, 2021 ; Igarashi et al, 2021 ; Lin et al, 2021 ; Lytle et al, 2020 ; Pauly et al, 2021 ; Pearman et al, 2021 ). Two articles focused on factors related specifically to age—ageism and subjective age ( Avidor et al, 2021 ; Lytle et al, 2020 )—one examined racial differences in psychological vulnerability during the COVID-19 pandemic ( Pearman et al, 2021 ), and two studies evaluated factors associated with loneliness ( Lin et al, 2021 ; Pauly et al 2021 ). Regarding the effects of ageism, Lytle et al (2020) found that young adults’ ageism toward older adults (measured prior to the pandemic) predicted their lower intentions to help older adults during the pandemic.…”
mentioning
confidence: 99%
“…Two articles focused on factors related specifically to age—ageism and subjective age ( Avidor et al, 2021 ; Lytle et al, 2020 )—one examined racial differences in psychological vulnerability during the COVID-19 pandemic ( Pearman et al, 2021 ), and two studies evaluated factors associated with loneliness ( Lin et al, 2021 ; Pauly et al 2021 ). Regarding the effects of ageism, Lytle et al (2020) found that young adults’ ageism toward older adults (measured prior to the pandemic) predicted their lower intentions to help older adults during the pandemic. This finding suggests that willingness to engage in supportive behaviors toward older adults during the pandemic may be negatively influenced by preexisting age-related biases.…”
mentioning
confidence: 99%